Biallelic DAB1 Variants Are Associated With Mild Lissencephaly and Cerebellar Hypoplasia. (April 2021) - Smits, Daphne J.; Schot, Rachel; Wilke, Martina; van Slegtenhorst, Marjon; de Wit, Marie Claire Y.; Dremmen, Marjolein H.G.; Dobyns, William B.; Barkovich, A. James; Mancini, Grazia M.S.
Abstract : Objective: We aimed to identify pathogenic variants in a girl with epilepsy, developmental delay, cerebellar ataxia, oral motor difficulty, and structural brain abnormalities with the use of whole-exome sequencing. Methods: Whole-exome trio analysis and molecular functional studies were performed in addition to the clinical findings and neuroimaging studies. Results: Brain MRI showed mild pachygyria, hypoplasia of the cerebellar vermis, and abnormal foliation of the cerebellar vermis, suspected for a variant in one of the genes of the Reelin pathway. Trio whole-exome sequencing and additional functional studies were performed to identify the pathogenic variants. Trio whole-exome sequencing revealed compound heterozygous splice variants in DAB1, both affecting the highly conserved functional phosphotyrosine-binding domain. Expression studies in patient-derived cells showed loss of normal transcripts, confirming pathogenicity. Conclusions: We conclude that these variants are very likely causally related to the cerebral phenotype and propose to consider loss-of-function DAB1 variants in patients with RELN-like cortical malformations.